2000
DOI: 10.1007/s003920070096
|View full text |Cite
|
Sign up to set email alerts
|

Role of pericytes in vascular calcification: a review

Abstract: Pericytes are defined by their location in vivo; the pericyte partially surrounds the endothelial cell of the microvessel and shares a common basement membrane with it. As an integral part of the microvasculature, pericytes play a fundamental role in maintaining local and tissue homeostasis. Current evidence also suggests that pericytes function as progenitor cells capable of differentiating into a variety of different cell types including osteoblasts, chondrocytes and adipocytes. It is now apparent that cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
75
1
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 0 publications
4
75
1
3
Order By: Relevance
“…This data therefore appears in agreement with previous reports, which showed that MEM could be successfully employed in culture of cells expressing smooth muscle cell markers (pericytes or calcifying vascular cells). Indeed, these cells routinely cultured in MEM spontaneously formed multicellular nodules that mineralized without exogenous factors (Schor et al, 1995;Proudfoot et al, 1998;Canfield et al, 2000). However, in order to explain the lower proportion of SMA+ cells in RPMI 1640 medium, we can hypothesize that the high phosphate concentration (5mM) had induced a phenotypic transition characterized by a loss of α-smooth muscle actin as previously described in bovine aortic smooth muscle cells (Steitz et al, 2001).…”
Section: Discussionmentioning
confidence: 75%
“…This data therefore appears in agreement with previous reports, which showed that MEM could be successfully employed in culture of cells expressing smooth muscle cell markers (pericytes or calcifying vascular cells). Indeed, these cells routinely cultured in MEM spontaneously formed multicellular nodules that mineralized without exogenous factors (Schor et al, 1995;Proudfoot et al, 1998;Canfield et al, 2000). However, in order to explain the lower proportion of SMA+ cells in RPMI 1640 medium, we can hypothesize that the high phosphate concentration (5mM) had induced a phenotypic transition characterized by a loss of α-smooth muscle actin as previously described in bovine aortic smooth muscle cells (Steitz et al, 2001).…”
Section: Discussionmentioning
confidence: 75%
“…Cellular transformation to a myofibroblastic phenotype commonly occurs during wound healing and tissue injury (32). Pericytes have been indicated to function as progenitor cells capable of differentiating into a variety of cell types and synthesizing collagen during inflammation, injury repair, or angiogenesis (6,11). In particular, PAF, normally released by activated leukocytes and endothelial cells during inflammation, has been reported to be able to act as a direct cytokine and stimulate lung pericyte growth in vitro (24).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, pericytes may be involved in the development and progression of several pathological conditions, including vascular calcification. 30,31 Indeed, markers of both cartilage and bone have been identified in calcified blood vessels, [31][32][33][34][35] and it has been suggested that a subpopulation of SM cells that resemble pericytes (calcifying vascular cells) contributes to this calcification. 30 -32 A recent study has shown that these cells also have multilineage potential in vitro.…”
Section: Discussionmentioning
confidence: 99%